2018
DOI: 10.3390/ijerph15081739
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Verification of Bloom-forming Aphanizomenon flos-aquae and Their Secondary Metabolites in the Nakdong River

Abstract: Aphanizomenon spp. have formed harmful cyanobacterial blooms in the Nakdong River during spring, autumn, and now in winter, and the expansion of blooming period and area, associated with the global warming is predicted. The genus Aphanizomenon has been described to produce harmful secondary metabolites such as off-flavors and cyanotoxins. Therefore, the production of harmful secondary metabolites from the Aphanizomenon blooms in the Nakdong River needs to be monitored to minimize the risk to both water quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…To date, few studies have evaluated the presence of several genes of clusters responsible for biosynthesis of microcystin, cylindrospermopsin and saxitoxin in environmental samples [11,[27][28][29][30][31][32][33][34][35], when compared to the majority of studies in which only one gene is used. Of these, five [28,30,[33][34][35] reported results similar to those obtained in this work, i.e., differential amplification between genes responsible for biosynthesis of a cyanotoxin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, few studies have evaluated the presence of several genes of clusters responsible for biosynthesis of microcystin, cylindrospermopsin and saxitoxin in environmental samples [11,[27][28][29][30][31][32][33][34][35], when compared to the majority of studies in which only one gene is used. Of these, five [28,30,[33][34][35] reported results similar to those obtained in this work, i.e., differential amplification between genes responsible for biosynthesis of a cyanotoxin.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanotoxins are large groups of secondary metabolites which are toxic to most eukaryotic organisms and can be classified according to their mechanism of action: neurotoxic (anatoxin-a and analogues, saxitoxin and analogues), hepatotoxic (microcystins and nodularins), dermatotoxic (lipopolysaccharides) and cytotoxic (cylindrospermopsins) [6][7][8]. Some species and genera, such as Microcystis aeruginosa, Raphidiopsis raciborskii (Woloszynska) Aguilera, Berrendero Gómez, Kastovsky, Echenique and Salerno (basionym Cylindrospermopsis raciborskii (Woloszynska) Seenayya and Subba Raju) [9], Planktothrix and Dolichospermum have been numerously reported to produce toxins [7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aphanizomenon is usually reported in the summer, before and after Microcystis blooms, in the Nakdong River. However, serious blooms of Aphanizomenon have been observed in winter in the Nakdong River since 2015 (Park et al, 2018). We found that the December nCCCs were mainly influenced by the relative abundance of Aphanizomenon and by discharge (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The most predominant bloom‐forming cyanobacterial species in rivers were Microcystis , Anabaena , Oscillatoria , and Phormidium (Hong et al., 2018; Hur et al., 2013; Lee et al., 2018). Several studies examined how different environmental conditions affect the cyanobacterial composition and the production of harmful secondary metabolites in rivers (Kim et al., 2017; Lee et al., 2018; Park et al., 2018; Srivastava et al., 2015). Shifts in the population dynamics and toxin production were often reported due to nutrient and physical factors (Srivastava et al., 2015).…”
Section: Introductionmentioning
confidence: 99%